2017
DOI: 10.1111/cas.13415
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal adenocarcinoma microenvironment: Peritumoral adipose tissue effects associated with chemoresistance

Abstract: Peritumoral microenvironment affects cancer development and chemoresistance, and visceral adipose tissue may play a critical role. We aimed to identify depot‐specific adipose characteristics associated with carcinogenesis and resistance to neoadjuvant therapy in esophageal adenocarcinoma (EAC). We analyzed: (i) the peritumoral adipose tissue of rats following the induction of esophageal carcinogenesis; (ii) the peritumoral and distal (omental) adipose tissue of patients affected by EAC; (iii) adipose‐derived s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…6 Carraro et al also demonstrated that the peritumoral microenvironment played an important role in tumor resistance to neoadjuvant therapy. 7 To further improve therapeutic strategy precision, however, a range of peritumoral regions impacting on different tasks is required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Carraro et al also demonstrated that the peritumoral microenvironment played an important role in tumor resistance to neoadjuvant therapy. 7 To further improve therapeutic strategy precision, however, a range of peritumoral regions impacting on different tasks is required.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Evans et al reported that the peritumoral microenvironment was significantly associated with progression and metastasis in head and neck squamous cell carcinoma 6 . Carraro et al also demonstrated that the peritumoral microenvironment played an important role in tumor resistance to neoadjuvant therapy 7 . To further improve therapeutic strategy precision, however, a range of peritumoral regions impacting on different tasks is required.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, to investigate the association between SCCA1 and the peritumoral microenvironment, we evaluated SCCA1 expression, stem cell markers, and paracrine adipose tissue mediators in peritumoral adipose tissue that had been proven to play a significant role in the nodal metastatic process and in chemoresistance . In our series, SCCA1 expression within the tumor was inversely correlated with CD34 levels, both within the tumor and in the peritumoral adipose tissue.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, these results agree with the recent report of a direct association between SCCA1 and the expression of immune checkpoint regulators PD‐L1/PD‐L2 in head and neck squamous cell carcinoma . Interestingly, in a very recent multicohort, phase IB study, pembrolizumab, an anti‐PD‐L1 Ab, showed manageable toxicity and durable antitumor activity in patients with heavily pretreated, PD‐L1‐positive advanced esophageal carcinoma . The increased levels of PD‐L1 expression in EAC, induced by SCCA1, might contribute to the observed intratumoral immune impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation